Conversor multifuncional recongurável e tolerantes a falhas para microrredes de energia elétrica - Hélio Marcos André Antunes (2018)
In AC microgrids, it is interesting to create a new converter topology that aggregates a single structure to the three essentials converters in AC microgrids, dened as gridfeeding, grid-forming and grid-supporting. One converter that can be modied to obtain a multifunctional conguration is the series protection dynamic device. This converter is connected in series with the power grid without galvanic isolation, which assures compensation of the main phenomenon which reduces power quality linked to voltage waveform.Inthisthesis, a multifunctional converter is proposed based on the series dynamic protection device and applied to AC microgrids with centralized control architecture, that can be single-phase or three-phase three- or four-wire networks. As well as developing the typical functionalities of microgrid converters, the proposed converter can switch its connection topology from series to parallel and vice-versa, depending on the powergrid and microgrid needs. The developed control algorithm allows on-line change of the converter operation either as a voltage- or current-controlled source. Moreover, it is possible to make a smooth transition between microgrid operation modes. This exibility allows the converter to operate as: (i) grid-forming applying voltage reference and managing black-start; (ii) grid-feeding injecting active power; and (iii) grid supporting performing ancillary services such as voltage regulation, voltages a gands well compensation, along with series or shunt active power ltering of reactive, unbalance and harmonic compensation. The multifunctional control is implemented using a Texas Instruments TMS320F28335 digital signal processor and then validated through a hardware-in-the-loop simulation developed into a Typhoon HIL 600 platform. By contrast operating as a grid-forming converter in AC microgrids, the multifunctional converter has a fault tolerance feature. In this condition, three single-phase inverters are connected in delta, forming a three-phase three-wire system. With a zig-zag transformer connection in the converters output, it is also possible to create a three-phase four-wire system. Besides creating a voltage and frequency reference, the converter can change its conguration from delta to open-delta and vice versa, without interrupting the supply of the microgrid with an eventual failure in one of the single-phase inverters. Experimental results are shown to validate the fault tolerant converter operation.